2021
DOI: 10.1111/nph.17878
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome interacting factor 3 regulates pollen mitotic division through auxin signalling and sugar metabolism pathways in tomato

Abstract: The development of viable pollen determines male fertility, and is crucial for reproduction in flowering plants. Phytochrome interacting factor 3 (PIF3) acts as a central regulator of plant growth and development, but its relationship with pollen development has not been determined.Through genetic, histological and transcriptomic analyses, we identified an essential role for SlPIF3 in regulating tomato (Solanum lycopersicum) pollen development. Knocking out SlPIF3 using clustered regularly interspaced short pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 64 publications
(92 reference statements)
0
13
0
Order By: Relevance
“…While many studies have identified the roles of sugars in pollen maturation and germination stages of pollen grain development, our study proposes similar roles of sugars during the early stages of pollen development, where maintaining optimum assimilation flow and sugar levels are crucial during microsporogenesis as well as microgametogenesis. In our recent study we identified that in the development of pollen in tomato mitotic division was also regulated through auxin signaling and sugar metabolism pathways [ 47 ]. Additionally, current studies show that starch and sugar are involved in pollen development, as reported in the articles ‘Deficiency of rice hexokinase HXK5 impairs synthesis and utilization of starch in pollen grains and causes male sterility’ [48] and ‘Comparative analysis of the transcriptome, methylome, and metabolome during pollen abortion of a seedless citrus mutant’ [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have identified the roles of sugars in pollen maturation and germination stages of pollen grain development, our study proposes similar roles of sugars during the early stages of pollen development, where maintaining optimum assimilation flow and sugar levels are crucial during microsporogenesis as well as microgametogenesis. In our recent study we identified that in the development of pollen in tomato mitotic division was also regulated through auxin signaling and sugar metabolism pathways [ 47 ]. Additionally, current studies show that starch and sugar are involved in pollen development, as reported in the articles ‘Deficiency of rice hexokinase HXK5 impairs synthesis and utilization of starch in pollen grains and causes male sterility’ [48] and ‘Comparative analysis of the transcriptome, methylome, and metabolome during pollen abortion of a seedless citrus mutant’ [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be the reason for the morphological changes in the epidermal cells of mutant anthers. In addition, recent studies have shown that the auxin signalling pathway regulates pollen mitotic division [ 36 ]. The expression levels of genes involved in plant hormone signal transduction were higher in mutant than WT anthers just prior to dehiscence.…”
Section: Resultsmentioning
confidence: 99%
“…3b ). In tomato, SlMAPK4 (MITOGEN-ACTIVATED PROTEIN KINASE 4), SlMAPK20, and SlPIF3 (PHYTOCHROME INTERACTING FACTOR 3) have been demonstrated to play critical roles in microgametogenesis and specifically regulate post-meiotic pollen development through the sugar and auxin metabolism and signaling pathway [ 68 70 ]. Knockdown of SlMAPK20 or SlMAPK4 resulted in abnormally degraded cytoplasm at the binucleate stage of pollen development [ 68 , 69 ].…”
Section: Male Sterilitymentioning
confidence: 99%
“…Knockdown of SlMAPK20 or SlMAPK4 resulted in abnormally degraded cytoplasm at the binucleate stage of pollen development [ 68 , 69 ]. SlPIF3 mediates the pollen mitosis I process by directly promoting the expression of both SlGLT1 ( GLUTAMATE SYNTHASE 1 ) and SlCWIN9 ( CELL WALL INVERTASE 9 ) in the tomato anther [ 70 ]. Knockout of SlGLT1 / SlCWIN9 phenocopied the defective bicellular pollen phenotypes of Slpif3 mutants [ 70 ].…”
Section: Male Sterilitymentioning
confidence: 99%